The Elimination Effect of Medical-Grade Honey on Pseudomonas aeruginosa Biofilms: A Systematic Review and Meta-Analysis - Hariyudo, Hariyudo; Benokri, Hasan Rizky; Wirohadidjojo, Yohanes Widodo; Herdini, Camelia; Budiyanto, Arief; Nugroho, Dhite Bayu (Journal of Clinical Medicine Research, 2025)
Background: This systematic review aimed to evaluate the efficacy of medical-grade honey (MGH) in eliminating and inhibiting Pseudomonas aeruginosa (P. aeruginosa) biofilms, which are known for their resistance to conventional antibiotics and significant role in chronic infections. Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines and registered in PROSPERO (CRD42024614542), a systematic search was conducted across PubMed, ProQuest, Scopus, and EBSCO using terms related to P. aeruginosa, biofilm, and MGH. Inclusion criteria encompassed in vitro studies assessing MGH’s effect on P. aeruginosa biofilms, with reported outcomes including biofilm inhibition and eradication. Data extraction and risk-of-bias assessment were performed independently by two reviewers using the Quality Assessment Tool for In Vitro Studies (QUIN) tool. Publication bias was estimated through forest plot. Results: A total of 1,934 records were identified from four databases. After screening and full-text review, six in vitro studies met the inclusion criteria for qualitative synthesis, and five were eligible for meta-analysis. All studies evaluated the effect of MGH, including Manuka and Surgihoney, on P. aeruginosa biofilms using crystal violet staining and spectrophotometric analysis. Pooled results showed that MGH significantly reduced biofilm formation (standardized mean difference (SMD) = -4.98; 95% confidence interval (CI): -6.72 to -3.25) and effectively disrupted established biofilms (SMD = -4.44; 95% CI: -6.62 to -2.26). Subgroup analysis revealed stronger effects on American Type Culture Collection (ATCC) strains than clinical isolates, with low within-subgroup heterogeneity. MGH also demonstrated significant superiority compared to active biofilm controls, although sterility control comparisons showed high variability. Mechanistic analysis found that Medihoney outperformed sugar solutions and methylglyoxal (MGO) alone, suggesting that its antibiofilm activity results from synergistic bioactive compounds. Overall, these findings support MGH as a potent antibiofilm agent, warranting further research for clinical application against P. aeruginosa biofilm infections. Conclusion: MGH exhibits consistent and substantial anti-biofilm activity against P. aeruginosa in vitro, affecting both biofilm formation and established biofilms. These findings support its potential application as a topical therapeutic agent in managing biofilm-related infections, particularly in chronic wounds. Future research should prioritize standardized application protocols and investigate synergistic effects with conventional antimicrobials through clinical trials.